Programmable models of growth and mutation of cancer-cell populations - Bortolussi, Luca; Policriti, Alberto (Electronic proceedings in theoretical computer science, 2011)
In this paper we propose a systematic approach to construct mathematical models describing populations of cancer-cells at different stages of disease development. The methodology we propose is based on stochastic Concurrent Constraint Programming, a ﬂexible stochastic modelling language. The methodology is tested on (and partially motivated by) the study of prostate cancer. In particular, we prove how our method is suitable to systematically reconstruct different mathematical models of prostate cancer growth --together with interactions with different kinds of hormone therapy-- at different levels of reﬁnement.